Ultra-processed food consumption in Iceland - utilizing the NOVA food classification system - Rut Arnardóttir 1974- (2022)
Background: Food environments have changed over the last decades, and the consumption of ultra-processed foods (UPF) has increased globally. Ultra-processed foods are mostly energy-dense, high in sugars and fat, but low in fibre, protein, minerals and vitamins. This study aimed to examine the consumption of ultra-processed food among adults in Iceland. Methods: This cross-sectional study uses data from the Icelandic Dietary Survey 2019/2021, including 822 adults aged 18-81 years. The estimated food intake from ultra-processed food came from daily relative energy intake of ultra-processed food (% of total energy intake) from data obtained by two 24h food recalls. The NOVA classification system was used to classify food and drinks into four groups, unprocessed or minimally processed food, processed culinary ingredients, processed foods and ultra-processed foods. Consumption of ultra-processed foods was assessed according to sex, age groups, Body Max Index, education level and financial capability. Results: On average, Icelanders consumed 2.221 kcal daily, with 42% coming from ultra-processed food. Consumption was higher in the youngest age groups of males and females, 18-39 years (45% and 46%), compared to the oldest group of males and females, 60 years and older (38% and 39%) (p<0.001), with no significant difference between other factors. Diet quality was lower with higher consumption of ultra-processed food in both sexes; fibre intake among females was at 16 g/day (p=0.009). While protein intake decreased among quartiles from 25E% to 16E% amongst males (p<0.001) and 22E% down to 15E% amongst females (p<0.001). Also, added sugar intake increased among quartiles from 3E% to 10E% amongst males (p<0.001) and 3E% to 12E% amongst females (p<0.001). Conclusion: The proportion of UPF in the Icelandic diet is almost half of their daily energy intake. A higher contribution of UPFs was, in general, associated with lower dietary quality, low intake of fibres, and higher sugar content. Further studies are ...